Observed crustal uplift near the Southern Patagonian Icefield constrains improved viscoelastic Earth model - Lange, H. (2014)
Thirty‒one GPS geodetic measurements of crustal uplift in southernmost South America determined extraordinarily high trend rates (> 35 mm/yr) in the north‒central part of the Southern Patagonian Icefield. These trends have a coherent pattern, motivating a refined viscoelastic glacial isostatic adjustment model to explain the observations. Two end‒member models provide good fits: both require a lithospheric thickness of 36.5 ± 5.3 km. However, one end‒member has a mantle viscosity near η =1.6 ×1018 Pa s and an ice collapse rate from the Little Ice Age (LIA) maximum comparable to a lowest recent estimate of 1995–2012 ice loss at about −11 Gt/yr. In contrast, the other end‒member has much larger viscosity: η = 8.0 ×1018 Pa s, half the post–LIA collapse rate, and a steadily rising loss rate in the twentieth century after AD 1943, reaching −25.9 Gt/yr during 1995–2012.